Student Anxiety and Education: Effects in the Secondary Foreign Language Classroom - Brynja Björk Reynisdóttir 1993- (2018)
In recent years, anxiety has become a prevalent topic in many academic fields, and numerous studies can be found that analyze and provide methods for reducing anxiety. However, in Iceland, further study is necessary: especially with regard to general pedagogy, foreign language learning, and secondary education. Therefore, this thesis will endeavor to describe English foreign language anxiety in Iceland based on applicable literature, student and instructor perspectives, and a comparison of qualitative research results from three secondary schools. Similarly, the main hypothesis is that student surveys and instructor interviews will show that students struggle in their foreign language courses and require additional help from instructors in three key areas: speaking, assessments, and social interactions. Participants from a variety of age ranges (between 16 and 25) at the upper-secondary level were chosen from three schools. 15 of the most pertinent questions were taken from the 33 item Foreign Language Classroom Anxiety Scale (FLCAS) developed by Horwitz, E., Horwitz, M., & Cope, J. (1986). Four short answer questions were also included to further assess student perspectives. These 19 questions were chosen based on their relevance to secondary schools in general, to the Icelandic classroom, and to the learning contexts discussed in both the theoretical and methodological sections of this thesis. Results show that the two forms of anxiety that students struggle with the most are speaking and social anxiety. Keywords: anxiety, social, speaking, assessment, pedagogy, foreign language, classroom, student perspectives, qualitative research, secondary education.